Redeployment in language contact: the case of phonological emphasis - Flynn, Darin (Frontiers in Language Sciences, 2024)
This article applies the notion of redeployment in second language acquisition to contact-induced diachronic changes. Of special interest are cases where a marked phonological contrast has spread across neighbouring languages. Such cases suggest that listeners can re-weight and re-map phonetic cues onto novel phonological structures. On the redeployment view, cues can indeed be re-weighted, but phonological structures which underlie a new contrast are not expected to be fully novel; rather, they must be assembled from preexisting phonological structures. Emphatics are an instructive case. These are (mostly) coronal consonants articulated with tongue-root retraction. Phonological emphasis is rare among the world's languages but it is famously endogenous in Arabic and in Interior Salish and it has spread from these to not a few neighbouring languages. Some of these neighbouring languages acquired emphatics by redeploying the phonological feature [RTR] (retracted tongue root) from preexisting uvulars. Others acquired emphatics by redeploying their consonantal use of [low] in preexisting pharyngeals. Phonological emphasis is apparently not borrowed by neighbouring languages where consonants lack a phonological feature fit for redeployment.